Public Space and the Public Sphere: The Legacy of Neil Smith. (18th September 2015) - Low, Setha
Abstract: This article attempts to untangle two threads of the intellectual and political legacy of Neil Smith. The first concerns the work that Neil and I did together on the The Politics of Public Space (Low and Smith2006, Routledge) on public space and the public sphere and then explains how our paths diverged. I elaborate some of the ways that the public space and public sphere have been expanded by later researchers and that left me with a sense of optimism about the future of public space as a forum for new social and political encounters. The second part of the discussion turns to Neil's thinking and writing as he moved away from having any faith in liberal urban policy, and his conclusion that neoliberalism was waning. Drawing upon publications by his students, I have attempted to assess the impact of his work—particularly on anthropology students focusing on his contribution to gentrification as a global urban strategy and his later turn to revolution as the necessary corrective to the death of neoliberalism. I contrast his revolutionary imperative with my desire to imagine new kinds of translocal public spaces that could expand into a global public sphere.